Formulaic style of oral poetry of Turkic peoples - Tuimebayev, Zhanseit K.; Amanzholova, Jemma B.; Zhanabayev, Kairat; Turgenbayeva, Aizhan Sh. (The New Research of Tuva, 2025)
The article analyzes the characteristics of the formulaic style in the oral poetry of Turkic peoples, focusing on its rhythmic, lexical, and syntactic properties, as well as identifying the functional nature of formulaic units. The analysis is based on the oral tradition theory developed by M. Parry and A. B. Lord. The study examines groups of words that are regularly used in identical metrical conditions to convey a given central idea in poetic texts of Kazakh, Nogai, Karakalpak, and Crimean Tatar zhyrau traditions, as well as in samples of Tuvan ritual lyrics. The analysis has established that sound repetitions not only provide a compositional framework and support the rhythmic organization of the text but also serve an important suggestive function. Anaphoric formulas create an effect of magical incantation and connection with sacred forces, while monorhymed repetitions, along with seven- and eight-syllable verse structures, facilitate memorization and the transmission of texts across generations. As a stylistic device, the formula enhances the imagery and expressiveness of oral speech. It reinforces the dynamics of imagery and intonation while rhythmically structuring speech. The study of the sound structure and traditional semantics of Turkic oral poetry has revealed the complex phonetic and functional nature of its various formulaic units, leading to a deeper understanding of the connection between sound formulas and their primary transformations — rhythmic incantations, magic, and suggestion.